(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Customer satisfaction is one of the most important goals that all organizations seek to achieve. Customer satisfaction means achieving full loyalty to the organization, thus gaining market share and entering into the midst of intense competition. The present study aimed at clarifying the theoretical concepts of hotel service quality and customer satisfaction. It aims to demonstrate the impact of hotel quality on customer satisfaction and customer satisfaction. The importance of the study is of the importance of the quality of the hotel service of excellent grade in Baghdad and the extent of customer satisfaction. The research is based on a basic premise that the quality of the hotel service affects the degree of customer satisfaction, and has resulted in three sub-hypotheses. In order to prove the validity of the hypothesis, the researcher designed a questionnaire form of three axes, the first dealt with the quality of the second hotel service, the customer satisfaction, and 20 questionnaires were distributed on the research sample of the Baghdad Hotel to a number of employees and employees, all of which were retrieved and subjected to statistical analysis Through the Statistical Analysis Program (SPSS). The study reached a number of conclusions, the most important of which is that the quality of the hotel service is related to the extent of the hotel’s management ability to provide services that match or exceed the customer’s expectations. The main recommendations of the study are that customers should feel safe in their dealings with the hotel in order to ensure customer loyalty and continuity in dealing with the hotel.